Large-scale network topology reveals brain functional abnormality in Chinese dyslexic children. (16th July 2021) - Zhang, Jia; Liu, Lanfang; Li, Hehui; Feng, Xiaoxia; Zhang, Manli; Liu, Li; Meng, Xiangzhi; Ding, Guosheng
Abstract: It has been revealed that dyslexic children learning alphabetic languages are characterized by aberrant topological organization of brain networks. However, little is known about the functional organization and the reconfiguration pattern of brain networks in Chinese dyslexic children. Using graph theoretical analysis and functional magnetic resonance images (fMRI), we examined this issue specifically from the perspective of functional integration and segregation. We first compared large-scale topological organizations between dyslexic children and typically developing children during a Chinese phonological rhyming task, and found that dyslexic children showed increased local efﬁciency and clustering coefficient compared with typically developing children, which were negatively correlated with task performance. Furthermore, dyslexic children and typically developing children could be accurately distinguished at the individual-subject level based on the nodal local efﬁciency or clustering coefficient. Second, we studied the group difference of network reconfiguration and found that dyslexic children showed more difficulty when shifting from the resting state to the phonological task. Our results suggest an over-segregated brain functional organization and deficits in brain network reconfiguration in Chinese dyslexic children, which helps to advance our knowledge on the neural mechanisms underlying dyslexia. Highlights: We compared large-scale functional organizations between Chinese dyslexic children and typically developing children. Chinese dyslexic children showed higher local efﬁciency and clustering coefficient than typically developing children. Chinese dyslexic children showed difficulties when shifting from the resting state to the phonological rhyming task. Chinese dyslexia associates over-segregated brain functional organization and deficits in brain network reconfiguration.